The Neuroendocrine-Immune Regulation in Response to Environmental Stress in Marine Bivalves - Liu, Zhaoqun; Li, Meijia; Yi, Qilin; Wang, Lingling; Song, Linsheng (Frontiers in Physiology, 2018)
Marine bivalves, which include abundant species distributed worldwide from the intertidal zones to hydrothermal vents and cold seeps, are important components of the ecosystem and biodiversity. In their living habitats, marine bivalves need to cope with a series of harsh environmental stresses including biotic threats (bacterium, virus, and protozoan) and abiotic threats (temperature, salinity, and pollutants). In order to adapt to these surroundings, marine bivalves have evolved sophisticated stress response mechanism, in which the neuroendocrine regulation plays an important part. Nervous system and hemocyte, which is the most important immunocyte in marine bivalves, are pillars of the neuroendocrine system. Various neurotransmitters, hormones, neuropeptides and cytokines have also been characterized to work as signal messengers or effectors, regulating humoral and cellular immunity, energy metabolism, shell formation, larval development, etc, in response against vast array of environmental stresses. In the present review, a substantial consideration will be devoted in outlining vital components of the neuroendocrine system identified from bivalves, as well as its modulation repertoire in response to environmental stresses, hoping to illustrate the dramatic adaptation mechanisms of molluscs.